(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The potential of new materialisms and queer theory are mirrored in a performative research methodology applied to the educational field. This inquiry articulates its results around the textile object/avatar YoYoYo, operating through a triple mimesis (Yo Yolanda Yocasta). Through an adult play methodology structured into seven thresholds, the work proposes a rupture with disciplinary rationality in academia. The praxis of becoming-rag enables a corporeal expansion that reorients the pedagogical environment. The use of textile avatars facilitates the emergence of an undisciplined materialism, where the researcher’s body becomes an aesthetic and political event in teacher training.